Factors Associated to Basic Emergency Obstetric Neonatal Care (BEONC) Nurses' Decision Making Skill - Ahsan, Ahsan; Dewi, Ni Luh Diah Ayu Sita; Haedar, Ali; Rahmawati, Ike Nesdia (Jurusan Keperawatan FIKES UNSOED, 2018)
Neonatal mortality rate (NMR) is an indicator to measure health degree of an area, health problem which involves some institutions to take a decision. The postponement of emergency condition recognition, attaining health facilities, and treatment are three theories of neonatal emergency postponement. The prominent problem of postponement of emergency condition recognition is nurse's ability to think critically to take a decision to determine emergency condition in neonatal. Critical thinking skill is an obligation competence for neonatal emergency nurses. Some theories reveal that characteristic of age, gender, educational background, training and tertiary education, working experience, and employment status influence nurses's decision making skill in treating neonatal emergency case. Different curriculum for introduction to critical thinking in treating neonatal emergency is a basis problem to be a neonatal emergency competent nurse. This research aims to analyze age, gender, education, advance training, experience, and employment status towards decision making skill neonatal emergency implementation at community health care center PONED. This research used cross sectional with purposive sampling. One hundred fifty three (153) nurses were invoked to be the subjects of this research. Besides, this research used Closed Ended Instrument. Based on the results of cross table, p value p>0.05 age, training, working experience and employment status were not related to decision making skill in emergency. Furthermore, male and bachelor of nursing science (p<0.05) is decision making skill of nurses in neonatal emergency. It is concluded that gender and nurse's educational background related to situation awareness. The results of this research are expected to encourage on service quality enhancement of neonatal emergency treatment.